2016
DOI: 10.1007/s12035-016-0140-8
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-Associated Membranes (MAMs): Overview and Its Role in Parkinson’s Disease

Abstract: Mitochondria-associated membranes (MAMs) are structures that regulate physiological functions between endoplasmic reticulum (ER) and mitochondria in order to maintain calcium signaling and mitochondrial biogenesis. Several proteins located in MAMs, including those encoded by PARK genes and some of neurodegeneration-related proteins (huntingtin, presenilin, etc.), ensure this regulation. In this regard, MAM alteration is associated with neurodegenerative diseases such as Parkinson's (PD), Alzheimer's (AD), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 145 publications
0
53
0
Order By: Relevance
“…Recently, it has been reported that perturbations in ER–mitochondria contacts have an important role in PD pathogenesis . Several studies have also revealed a potential link between familial PD and proteins known to cause defects in mitochondria .…”
Section: Abnormal Er–mitochondrial Crosstalk In Neurological Disordersmentioning
confidence: 99%
“…Recently, it has been reported that perturbations in ER–mitochondria contacts have an important role in PD pathogenesis . Several studies have also revealed a potential link between familial PD and proteins known to cause defects in mitochondria .…”
Section: Abnormal Er–mitochondrial Crosstalk In Neurological Disordersmentioning
confidence: 99%
“…Indeed, a growing body of evidence indicates that a defect in inter-organelle communication may play a role in the pathogenesis of multiple human diseases (30,33,59,60). More specifically, abnormalities associated with EMCs have been reported to be linked to multiple neurodegenerative disorders (20,30,61). However, the pathological mechanisms underlying these disorders remain to be fully clarified.…”
Section: Rtn1a Promotes Er-mitochondrial Contactsmentioning
confidence: 99%
“…To implement a variety of physiological functions, these organelles need to communicate and cooperate with each other via ion, metabolite, and lipid exchange at their contact sites (Rodríguez-Arribas et al 2016). MAMs, the best-characterized inter-organelle connections, were demonstrated to be a signaling hub in the regulation of cell processes, such as lipid exchange, Ca 2?…”
Section: Mitochondria-associated Er Membranesmentioning
confidence: 99%
“…homeostasis and ultimately induce apoptosis (Pizzo and Pozzan 2007). Furthermore, MAMs could also modulate cell function via the regulation of mitochondrial reactive oxygen species (ROS) production (Rodríguez-Arribas et al 2016). Previous studies indicated that MAMs are associated with numerous pathophysiological conditions, including Alzheimer's disease, Parkinson syndrome, and many other neurodegenerative disorders (Vance 2014).…”
Section: Introductionmentioning
confidence: 99%